HIV-1 entry inhibition capabilities of Isoflavones - Mr Steven Raubenheimer; Miss Phaladi Kunyane; Dr Mamoalosi Selepe; Dr Ntombenhle Gama (International Journal of Infectious Diseases)
Introduction: Over the years, HIV has persisted as a global health challenge. Although there is availability of anti-retroviral therapy, a cure remains elusive and the development of drug resistance to current drugs necessitates the development of novel therapies. This study investigated novel isoflavones that were synthesized from methoxybezofurans, a class of compounds that have been reported to exhibit anti-HIV activity. Methods: A subtype C pseudovirus, CAP 210 was produced through the co-transfection of HEK 293 T cells with the relevant plasmids, and the isoflavones were tested for their effects on the infectivity of these viruses using the BrightGlo luciferase substrate. Time of addition (TOA) studies were performed to elucidate the potential target of these compounds. These observations were supported by in silico docking studies. The effects of the compounds on the viability of TZM-bl cells were also determined. Results: The five isoflavones inhibited the infectivity of CAP 210, a subtype C pseudovirus, with IC50 values ranging between 6.2 and 10.6 µM. These were non-toxic to TZMbl cells, making the compounds highly selective to the virus (SI values range from 4.4 to 32.3). A modified time of addition (TOA) study was performed to ascertain entry inhibition and compounds B and C were identified as entry inhibitors. In silico docking studies revealed the compounds interact with Trp 427 and Glu 370 of gp120 via hydrogen bonding. Discussion: The development of novel HIV therapy remains a necessity for the sustainable management of HIV. This study identified five isoflavones with micromolar activities against HIV. Two of the five investigated compounds were shown to be entry inhibitors. There are currently, four FDA approved entry associated inhibitors, with only one, fostemsavir being an attachment inhibitor (interacting with gp120). Conclusion: Isoflavones have good HIV inhibition potential. The further development of these compounds could ultimately contribute to the collection of entry inhibitors in clinical use.